Martangiang di Tengah Dapur: Spiritualitas Perempuan Batak sebagai Ibadah Domestik dan Tempat Perjumpaan dengan Allah (Sekolah Tinggi Agama Kristen Arastamar Grimenawa J, 2025)
This study aims to reveal the meaning of Batak women's spirituality (ina partataring) through the practice of martangiang (prayer) performed in the kitchen as a hidden yet meaningful form of domestic worship. The research addresses the questions of how such domestic prayers reflect spiritual strength in the face of life’s limitations and how the kitchen is positioned as a sacred space in Batak culture. Employing a qualitative approach with a phenomenological method, this study explores the religious experiences of mothers through in-depth interviews and literature analysis on Batak culture and contextual theology. The findings show that the spirituality of Batak women does not depend on formal liturgical expressions, but is manifested in silence, sacrifice, and resilience within domestic spaces. The novelty of this research lies in its reinterpretation of the kitchen as a locus theologicus, or theological space, for Batak women—an aspect often overlooked in theological studies. This research offers a new discourse on contextual theology that centers women's spiritual experiences and broadens the understanding of faith practices in nonformal settings.